So Far and Yet so Close Frontier Cattle Ranching in Prairie Western Canada and the Northern Territory of Australia - Elofson, Warren (University of Calgary Press, 2015)
So Far and Yet So Close provides a comparative study of frontier cattle ranching in two societies on opposite ends of the globe. It is also an environmental history that at the same time centres on both the natural and frontier environments. There are many points at which the western Canadian and northern Australian cattle frontiers evoke comparisons. Most obviously they came to life at about the same time: late 1870s-early 1880s. In both cases corporations were heavy investors and utilized an open range system in which tens of thousands of cattle roamed over thousands of square acres. Ranchers shared similar problems such as predators, disease, and weather, as well as markets. Ultimately, a nearly indistinguishable "country" culture developed in these geographically disparate and distant lands, which is still apparent today. Many similarities were in one way or another a reflection of frontier environmental conditions that is, conditions associated with the very "newness" of society. They included a lack of infrastructure (ie. fences), institutions (ie. police), and population (ie. consumers). However, the ranching people in these two societies had their differences too. In the end, the natural environment pushed agricultural development in these two regions along very different paths.